Security Measures to Image Steganography and Steganalysis: An Overview - Dey, Dipankar; Samanta, Sabyasachi (International Journal of Psychosocial Rehabilitation, 2021)
Nowadays, the security system draws an important role to protect sensitive information from theft and implement data confidentiality, data integrity, authentication, and access controls. This article focuses on different parameters used to implement a security system in digital image processing. These parameters illustrate different mathematical and statistical analysis and state thestrongest point of an algorithm. These parameters are mainly used for image encryption, image steganography, image compression and Steganalysis etc. The optimized value of different analysis protects from different types of attacks such as Brute Force Attacks, Known plaintext Attacks, Statistical Attacks, Analytic Attacks, etc. The parameters are used to algorithm better which are Histogram Analysis, Information Entropy, NPCR, UACI, Correlations of two adjacent pixels, Key sensitivity, MSE, PNSR, NCC, AD, SC, MD, LMSE, NAE, SSIM, RMSE, etc. This article illustrates the application of these different statistical parameters on 512 × 512 grayscale and color images.